2016
DOI: 10.7567/jjap.55.022301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of buffer layer and back-surface field on MBE-grown InGaAsP/InGaAs solar cells

Abstract: Solid-state molecular beam epitaxy (MBE)-grown InGaAsP/InGaAs dual-junction solar cells on InP substrates are reported. An efficiency of 10.6% under 1-sun AM1.5 global light intensity is realized for the dual-junction solar cell, while the efficiencies of 16.4 and 12.3% are reached for the top InGaAsP and bottom InGaAs cells, respectively. The effects of the buffer layer and back-surface field on the performance of solar cells are discussed. High device performance is achieved in the case of a low concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Since Dimroth et al reported the wafer bonded four-junction GaInP/GaAs//GaInAsP/InGaAs solar cell with a highest efficiency of 46.0% at approximately 500 suns, [5] the InGaAsP solar cell has received more and more attention motivated by achieving higher conversion efficiency. [6][7][8][9][10][11][12] In this regard, a better understanding of the internal behaviors of carriers in InGaAsP solar cell should be desired. On the other hand, as is well known, quaternary alloy with different ionic radii is difficult to grow [13] because the miscibility gap inhibits the mixing of constituents within the alloy, different kinds of clustering (atomic ordering, quantumdots-like formations, and atomic content fluctuation, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Since Dimroth et al reported the wafer bonded four-junction GaInP/GaAs//GaInAsP/InGaAs solar cell with a highest efficiency of 46.0% at approximately 500 suns, [5] the InGaAsP solar cell has received more and more attention motivated by achieving higher conversion efficiency. [6][7][8][9][10][11][12] In this regard, a better understanding of the internal behaviors of carriers in InGaAsP solar cell should be desired. On the other hand, as is well known, quaternary alloy with different ionic radii is difficult to grow [13] because the miscibility gap inhibits the mixing of constituents within the alloy, different kinds of clustering (atomic ordering, quantumdots-like formations, and atomic content fluctuation, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The ternary In x Ga 1−x As alloy has gained great success on optoelectronic applications due to the tunable bandgap from 0.9~3 µm, which is corresponding to the atmosphere transmission window [1,2]. For example, In 0.53 Ga 0.47 As, which is lattice-matched to InP materials, has been widely used in multi-junction photovoltaics and commercially available in opto-communications [3][4][5][6]. In recent years, extended wavelength In x Ga 1−x As (x > 0.53) and derived quaternary alloy have attracted more and more attention in thermophotovoltaics (TPV), remote sensing, and thermal imaging [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%